Elderly population have a decreased aneurysmal subarachnoid hemorrhage incidence rate than Middle aged population: a descriptive analysis of 8, 144 cases in mainland China. (4th March 2018) - Wáng, Yì Xiáng J.; Zhang, Lihong; Zhao, Lin; He, Jian; Zeng, Xian-Jun; Liu, Heng; Yang, Yun-Jun; Ding, Shang-Wei; Xu, Zhong-Fei; He, Yong-Ming; Yang, Lin; Sun, Lan; et al.
Abstract: Purpose: Rupture of an intracranial aneurysm is a life-threatening acute cerebrovascular event. The purpose of this study was to investigate whether aneurysmal subarachnoid haemorrhage (SAH) incidence rate is higher or lower in elderly population than in middle aged population. Materials and methods: Aneurysmal SAH cases were collected retrospectively from the archives of 21 hospitals in Mainland China. All the cases were collected from September 2016 and backward consecutively for a period of time up to 8 years. SAH was initially diagnosed by brain computed tomography (CT). CT angiography (CTA) or digital subtraction angiography (DSA) was followed and SAH was confirmed to be due to cerebral aneurysm rupture. For cases when multiple bleeding occurred, the age of the first SAH was used in this study. The total incidence from all hospitals at each age group were summed together for females and males respectively; then adjusted by the total population number at each age group for females and males which was from the 2010 population census of the People's Republic of China. Results: In total there were 8, 144 cases of intracranial aneurysmal SAH, with 4, 861 females and 3, 283 males. For females the relative aneurysmal SAH incidence rate started to decrease after around 65 years old, while for males the relative aneurysmal SAH incidence rate started to decrease after around 53 years old. Conclusion: Our data tentatively suggest elderly patients may be at a reduced risk of rupture compared with patients who are younger while have similar other risk factors.